Activities of artesunate and primaquine against asexual- and sexual-stage parasites in falciparum malaria. - Pukrittayakamee, S; Chotivanich, K; Chantra, A; Clemens, R; Looareesuwan, S; White, N (2004)
The activities of primaquine in combination with quinine or artesunate against asexual- and sexual-stage parasites were assessed in 176 adult Thai patients with uncomplicated Plasmodium falciparum malaria. Patients were randomized to one of the six following 7-day oral treatment regimens: (i) quinine alone, (ii) quinine with tetracycline, (iii) quinine with primaquine at 15 mg/day, (iv) quinine with primaquine at 30 mg/day, (v) artesunate alone, or (vi) artesunate with primaquine. Clinical recovery occurred in all patients. There were no significant differences in fever clearance times, rates of P. falciparum reappearance, or recurrent vivax malaria between the six treatment groups. Patients treated with artesunate alone or in combination with primaquine had significantly shorter parasite clearance times (mean +/- standard deviation = 65 +/- 18 versus 79 +/- 21 h) and lower gametocyte carriage rates (40 versus 62.7%) than those treated with quinine (P < or = 0.007). Primaquine did not affect the therapeutic response (P > 0.2). Gametocytemia was detected in 98 patients (56% [22% before treatment and 34% after treatment]). Artesunate reduced the appearance of gametocytemia (relative risk [95% confidence interval] = 0.34 [0.17 to 0.70]), whereas combinations containing primaquine resulted in shorter gametocyte clearance times (medians of 66 versus 271 h for quinine groups and 73 versus 137 h for artesunate groups; P < or = 0.038). These results suggest that artesunate predominantly inhibits gametocyte development whereas primaquine accelerates gametocyte clearance in P. falciparum malaria.